1985
DOI: 10.1161/01.cir.71.4.840
|View full text |Cite
|
Sign up to set email alerts
|

Late phase of nitroglycerin-induced coronary vasodilatation blunted by inhibition of prostaglandin synthesis.

Abstract: In chloralose-anesthetized dogs with the left circumflex coronary artery perfused at constant flow, the effects of increasing doses of indomethacin or naproxen on the coronary and systemic hemodynamic responses to a 5 gg intracoronary injection of nitroglycerin (NTG) were evaluated. The integrated areas of NTG-induced coronary vasodilatation were reduced after administration of indomethacin or naproxen. The extent of this reduction was increased progressively by augmenting the dose of indomethacin and naproxen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Since there have been several studies which have suggested a role for prostacyclin or other vasodilatory prostaglandins in the antianginal actions of nitrates including ni corandil [Neichi et al, 1980;Schor et al, 1981;Nakabayashi et al, 1985;Trimarco et al, 1985], the present study was designed to test the hypothesis that the beneficial actions of nicorandil in the stunned myocardium were at least partially the result of an in crease in vasodilatory prostaglandins or a decrease in TxA2. The results clearly indicate that this is not the case, since indomethacin, in doses which produced nearly a 100% inhi bition of cyclooxygenase, did not block the salutory actions of nicorandil.…”
Section: Discussionmentioning
confidence: 99%
“…Since there have been several studies which have suggested a role for prostacyclin or other vasodilatory prostaglandins in the antianginal actions of nitrates including ni corandil [Neichi et al, 1980;Schor et al, 1981;Nakabayashi et al, 1985;Trimarco et al, 1985], the present study was designed to test the hypothesis that the beneficial actions of nicorandil in the stunned myocardium were at least partially the result of an in crease in vasodilatory prostaglandins or a decrease in TxA2. The results clearly indicate that this is not the case, since indomethacin, in doses which produced nearly a 100% inhi bition of cyclooxygenase, did not block the salutory actions of nicorandil.…”
Section: Discussionmentioning
confidence: 99%
“…Intervals of at least 2 weeks were allowed between two consecutive protocols in the same dog. The protocols [5][6][7] required acute laparatomy in anesthesia for place-ment of occlusive snares around arteries of the splanchnic bed or the hindquarter bed (Table 1). At the end of one of these protocols, the dogs were killed by an overdose of pentobarbital.…”
Section: Animals and Experimental Preparationmentioning
confidence: 99%
“…This mechanism may be responsible for the marked vasodilation induced by NTG and SNP. NTG, however, has also been shown to release prostaglan din (PGH) and subsequently stimulate the formation of cyclic AMP which also promotes vascular smooth muscle relaxation [26,27], The involvement of PGH has been reported to account for the persistence of reduction in cor onary resistance [28]. NTG-induced PGIi has been shown to contribute to the vasodilatory action of organic nitrates in the fetoplacental circulation [29].…”
Section: Discussionmentioning
confidence: 99%